A review on light-emitting diode based automotive headlamps. (January 2015) - Long, Xingming; He, Jugang; Zhou, Jing; Fang, Liang; Zhou, Xia; Ren, Fan; Xu, Tao
Abstract: Benefited from the fruitful results of general light-emitting diode (LED) lighting, the LED is utilized in the automotive forward lighting recently, the LED headlamp, due to its ability of improving the efficiency, durability and comfort of the automobile. Both the rough operating environments and rigorous safety standards make the design and verification of the LED headlamp face more challenges than that of the general LED lighting. Although there are some concerns about the status of the LED headlamp, these efforts mostly focused on a single issue, and little knowledge has been established from a system-level aspect. To obtain an up-to-date and systematical summary of the progress of the LED headlamp, in this review, after a description of the fundamentals of the LED headlamp, its design methods are scanned firstly following the categorized components: the LED array module, the heat management, optics control as well as the driver electronics; then, the verifications of the LED headlamp are explored according to the plug-in efficiency, cost, lifetime and reliability; next, the trends of the LED headlamp with the additional function of data transmission and integration of human factors are illustrated; and a conclusion is given finally. The results show that the LED headlamp is a complex electrical–optical–thermal–mechanical system, involved human factors; currently it reaches the state-of-the-art on the efficiency, while the cost is about 350% more than that of the halogen headlamps; additionally, the lifetime and reliability issues, which are closely related with the junction temperature and the moisture diffusion, least understands in human response to LED light as well as immature regulations do challenge the development of LED headlamp. However, the system-level, functional and human factors based solutions cast a light on the future LED headlamp.